IMPLICATION OF ACTIVE VIDEO GAMES IN THE TREATMENT AND PREVENTION OF OVERWEIGHT AND OBESITY IN THE PAEDIATRIC POPULATION - Benedykt Baljon; Justyna Bogdan; Radosław Ramotowski; Izabela Harpula; Patryk Brzezicki; Paulina Frączkiewicz; Natalia Bębenek; Gabriela Barszcz; Monika Błądek; Karolina Drygała; Sylwia Wit (International Journal of Innovative Technologies in Social Science, 2026)
Background: Active video games (AVG) are increasingly recommended as an attractive way to motivate overweight and obese children to include physical activity in their daily routines. However, the consistency and impact on weight, BMI, body composition, fitness, and health improvement remain uncertain and require further trials to examine their effects on children’s bodies. Objectives: To systematically review and collect evidence from systematic reviews, meta-analyses, and randomised controlled trials (RCTs) on how AVGs affect overweight and obese children. Methods: A comprehensive search was performed on PubMed, Scopus, and Web of Science for English-language articles published between 2020 and 2025. Selected studies included systematic reviews, meta-analyses, and RCTs evaluating AVG interventions in overweight or obese children aged 2–18, focusing on at least one weight or fitness-related outcome. Seven studies met the inclusion criteria. Results: Across included studies, AVGs were found to influence BMI-related and body composition outcomes. Evidence of improvements in cardiovascular and respiratory function was noticeable, especially when exergaming was combined with multicomponent exercise training. One of the RTCs reported an increase in muscle mass and motor skills. Conclusions: AVGs appear to be a safe and engaging method for improving BMI and body composition and providing additional benefits in cardiorespiratory fitness, muscular strength, and motor competence. The most consistent and clinically significant effects occur when exergaming is incorporated into structured, multicomponent exercise programs that last long enough. Further high-quality, adequately powered RCTs are needed to better understand the long-term effects on weight and optimise intervention strategies.